Compound Karst Cave Treatment and Waterproofing Strategy for EPB Shield Tunnelling in Karst Areas: A Case Study - Kang, Yongshui; Geng, Zhi; Lu, Linhai; Chen, Lei; Liu, Xuewei; Liu, Bin; Huang, Xing (Frontiers in Earth Science, 2021)
There is high risk of water inrush and ground collapse accident when tunnelling in karst area. Based on the case study of an urban metro tunnel, this paper focuses on karst cave treatment and waterproofing strategy for earth pressure balancing (EPB) shield tunnelling in karst area containing large amount of karst caves and fissures. When the shield machine enters karst area, water gush easily occurs, posing serious threat to tunnelling safety. The distribution characteristic of limestone fractures, karst caves and fissures in the karst area were analyzed according to the geological survey results. Further, water inrush risk and engineering difficulties were analyzed. Subsequently, a compound karst cave treatment and waterproofing strategy for EPB shield tunnelling was proposed and implemented. Water inflow is successfully reduced and ground collapse accident is avoided using the compound karst cave treatment and waterproofing strategy.